2007
DOI: 10.1021/la7020098
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Nanoparticle Flocculates for Dry Powder Aerosol Formulation

Abstract: Uncontrolled agglomeration presents a formidable encumbrance to nanoparticle formulation as a dry powder for inhalation therapy. Spray-drying and freeze-drying of nanosuspensions has demonstrated some success in creating dry powders composed of agglomerated nanoparticles with appropriate aerodynamic properties. These controlled drying processes, however, may require an undesirable amount of excipient to maintain an active therapeutic while generating dry powders and may not offer the desired control over agglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…For a gglomeration, the addition of monovalent cations is a well known procedure resulting in the agglomeration of phospholipids, solid lipid nanoparticles, and nanosuspensions. 42,51,52 It was reported that different types of monovalent cations can be chosen in order to control the degree of agglomeration. 53 The order of the capability of monovalent cations to induce the initial phase of the agglomeration of large phospholipid vesicles was reported to be: Li + .…”
Section: Resultsmentioning
confidence: 99%
“…For a gglomeration, the addition of monovalent cations is a well known procedure resulting in the agglomeration of phospholipids, solid lipid nanoparticles, and nanosuspensions. 42,51,52 It was reported that different types of monovalent cations can be chosen in order to control the degree of agglomeration. 53 The order of the capability of monovalent cations to induce the initial phase of the agglomeration of large phospholipid vesicles was reported to be: Li + .…”
Section: Resultsmentioning
confidence: 99%
“…Inhaled drugs should ideally possess an aerodynamic diameter less than 5 µm for delivery into the ‘deep’ lung for local therapy or systemic absorption (Weers et al, 2010). Nanoparticles (<0.5 µm) are more likely to be exhaled, which may lead to dose variability (Shi et al, 2007). If delivered as a suspension, such small particles are also prone to particle growth due to Ostwald ripening and can suffer from uncontrolled agglomeration (Berkland, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1). This may be due to the deposition of nanoparticles on agglomerates during lyophilization or to cohesion between agglomerates as a result of drying (57). Furthermore, it was clear that the combination lyophilized powders had a broader distribution compared to the other two formulations (F1 and F2).…”
Section: Resultsmentioning
confidence: 99%